2014
DOI: 10.1371/journal.pbio.1001823
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Time-Resolved Microtomography Reveals the Mechanics of the Blowfly Flight Motor

Abstract: Time-resolved X-ray microtomography permits a real-time view of the blowfly in flight at a previously unprecedented level of detail, revealing how the tiny steering muscles work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 41 publications
5
128
0
Order By: Relevance
“…Froghoppers power their jumps with torques about the CTr joint and steer by controlling jump azimuth with the FTi joint [33]. In a similar vein, large indirect flight power muscles of most insects provide the mechanical energy required for flapping the wings, while smaller steering muscles determine its transformation into lift and drag by adjusting the stroke plane and the wing's angle of attack [34,35]. Our findings provide the prospect that such a control strategy is also common in walking insects with distinctly different leg posture and kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Froghoppers power their jumps with torques about the CTr joint and steer by controlling jump azimuth with the FTi joint [33]. In a similar vein, large indirect flight power muscles of most insects provide the mechanical energy required for flapping the wings, while smaller steering muscles determine its transformation into lift and drag by adjusting the stroke plane and the wing's angle of attack [34,35]. Our findings provide the prospect that such a control strategy is also common in walking insects with distinctly different leg posture and kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that high-amplitude wing motion is not achieved by the pulling of Ax1 because of contraction of I1 at the end of upstroke. Rather, I1 contraction acts to restrict amplitude at the end of downstroke (Walker et al, 2014); these results explain why I1 is active when stroke amplitude decreases (Heide, 1975 , the troponin complex goes through a conformational shift inducing tropomyosin to release the block on the active site. Myosin heads then bind to these active sites and induce actinmyosin filaments to slide over one another, causing muscle contraction.…”
Section: Axillary Sclerite 1 and Associated Musclesmentioning
confidence: 98%
“…The base of the I1 muscle is attached to the anepisternal ridge, whereas I2 is more internal and sits on the pleural apophysis (for apophysis, see Glossary) (Figs 5B, 6A, Movie 2). A recent X-ray tomography study (Walker et al, 2014) showed that the tendon connecting the I1 muscle to Ax1 is in a buckled state at the onset of downstroke, when the wing is above the wing hinge. It transitions from a buckled to a taut state as it approaches the end of the downstroke.…”
Section: Axillary Sclerite 1 and Associated Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their size allows for micro-sensor access to the inner organs, such as the heart, accessory pulsatile organs and tracheal system, in contrast to the preferred fly model organism, Drosophila. In Calliphoridae, the structural basis and mechanics of the flight apparatus, its control and energetics have been investigated in detail (Miyan and Ewing, 1985;Nachtigall, 1985;Ennos, 1987;Wisser, 1988;Nalbach, 1989;Dickinson and Tu, 1997;Walker et al, 2014). There is a disproportion of thorough research on the flight mechanism in flies in contrast to the aspect of gas exchange during flight.…”
Section: Introductionmentioning
confidence: 99%